Aplicação de biochar e impacto na qualidade física do solo e características morfofisiológicas do eucalipto - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2019)
The incorporation of biochar in the soil, which is prevenient of the pyrolysis of biomass, has been shown as a sustainable alternative to improve its physical attributes. In addition, the interaction of biochar and fertilization may result in a synergic effect on the soil, since it can increase the surface charges of the biochar turning it more reactive. This carbonaceous material has the potential to improve soil quality, which can be evidenced by the least limiting water range. Soils with a better quality allow plants to better acquire nutrients, raising the opportunity to reduce the fertilization used in operational levels. Thus, the objectives of this study were (i) avail the effect of the interaction of biochar and fertilization on the least limiting water range in a LATOSSOLO VERMELHO-AMARELO used for cultivation of Eucalyptus urograndis, (ii) analyze the leaf gas exchanges and the production of wood of Eucalyptus urograndis cultivated under different levels of fertilization and biochar application, (iii) investigate the reduction of 20% of the standard fertilization on the cultivation of Eucalyptus urograndis with or without biochar incorporation in the lines of transplantation. The experiment was done in São Jerônimo da Serra, Parana, Brazil. The soil was classified as LATOSSOLO VERMELHO-AMARELO Distrófico típico with A húmico. The experimental design was randomized blocks with split-plots, in a 2x3 scheme with four repetition, totalizing 24 experimental units. The first source of variation is the incorporation or not of 3,23 Mg ha-1 of biochar in the line of transplantation. The second source of variation is the fertilization in the standard operational doses (150 g plant-1 of 04-42-06 at 15 days, 200 g plant-1 of 15-05-30 + 1% of B and Zn at 90 days and 110 g plant-1 of KCl at 9 months), 20% reduction of the standard fertilization and absence of fertilization. After the transplantation of seedlings of Eucalyptus urograndis, it was done three evaluations of leaf gas exchanges on 96 plants with an infrared gas analyzer at three, six and twelve months. The least limiting water range was evaluated at three months after the transplantation in 360 undisturbed soil cores. The height, diameter at breast height and volume of the trees was evaluated at eighteen months on 96 plants. It was observed that at three months the biochar did not interacted with the fertilization and did not improve the soil quality. It was not possible to observe interaction between biochar incorporation and fertilization on the leaf gas exchanges of the plants of Eucalyptus urograndis. The plants on the soil that received biochar showed higher transpiration at leaf level. In addition, the reduction or absence of fertilization enhanced the assimilation of carbon and transpiration, however the leaf gas exchanges had no logical relation with the morphological variables. The absence or the reduction of fertilization of 20% resulted in lower diameter at breast height, height and volume of plants in relation of the standard fertilization.
Keywords: Eucalyptus urograndis; intervalo hídrico ótimo; trocas gasosas foliares; dendrometria; Eucalyptus urograndis; least limiting water range; leaf gas exchange; dendrometry; CNPQ::CIENCIAS AGRARIAS::AGRONOMIA